Ganoderma boninense Pat. from basal stem rot of oil palm (Elaeis guineensis) in Peninsular Malaysia - Ho, Yin Wan; Nawawi, A. (Universiti Pertanian Malaysia, 1985)
Several hundred sporophores of Ganoderma were collected from 5 - 40 years old palm trees infected with basal stem rot in 5 oil palm estates in Peninsular Malaysia. Based on the morphometric studies of the pores, dessepiments and basidiospores dimensions and other morphological characteristics, the sporophores were identified as belonging to a single species, G. boninense Pat.